Role of Central Bank of Iraq in Combating Money Laundering - Al Rubaie, Samah Hadi (Rechtsidee, 2024)
The Central Bank of Iraq (CBI) plays a pivotal role in addressing money laundering, a critical issue for global financial stability. With the enactment of the Iraqi Anti-Money Laundering and Counter-Terrorist Financing Law No. 39 of 2015, the CBI has taken significant steps to mitigate the risks associated with money laundering. The research aims to delineate the measures implemented by the CBI, including the establishment of the Money Laundering Office and the development of strict supervisory mechanisms. Findings suggest that despite the comprehensive legislative framework, challenges such as political instability and lack of transparency continue to undermine efforts. The CBI's involvement in rigorous supervision and the adoption of international cooperation are crucial to curbing money laundering practices. This study underscores the necessity for enhanced regulatory frameworks and continuous monitoring to effectively combat these financial crimes.Highlights: The Central Bank of Iraq has established significant legal and supervisory frameworks to combat money laundering, as highlighted by Law No. 39 of 2015. Despite robust legal measures, ongoing political and economic instability poses challenges to the effective enforcement of anti-money laundering regulations. International cooperation and stringent supervision are critical to enhancing the efficacy of anti-money laundering efforts in Iraq. Keywords: Central Bank of Iraq, money laundering, legislation, supervision, financial stability